Model of communicative constitution of organization in the management of Borobudur Temple - Nenny Wahyuni; Ahmad Sihabudin; Ridzki Rinanto Sigit (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The purpose of the research is to build a model of the communicative constitution of the organization to overcome the problem of differences in plans and develop a travel pattern of thematic visits with the storytelling method to overcome the buildup in Borobudur Temple, Central Java, Indonesia. The type of research used is a quality approach with data collection through observation, interviews, and documentation. The study’s results integrated communication and coordination between the Badan Otorita Borobudur and the governing body managing the Borobudur Temple Area. As a solution to the problem, the model of the communicative constitution of the organization integrates goals in the direction of the temple area through communication flows with membership negotiations, self-structuring, coordination of activities in corporate activities, and institutional positions between managers in organization communication activities and coordination. The model of the communicative constitution of the organization will be a solution to integrate the goals of several ministries with different objectives in managing the Borobudur Temple Area.